Self-Disclosure, social comparison, and social anxiety among gen z social media users - Faiza, Nabilah Ni’matul; Maryam, Effy Wardati (Empathy : Jurnal Fakultas Psikologi, 2024)
Social anxiety arises from the fear of being negatively judged by others during specific social activities or situations. This can influence an individual's self-acceptance anxiety, thereby posing a threat to Gen Z when engaging in self-disclosure and social comparison on social media. This study aims to determine whether there is a relationship between self-disclosure and social comparison with social anxiety among Gen Z social media users. This research employs a correlational quantitative method, and the sampling technique used in this study is accidental sampling. The subjects of this study are Generation Z individuals aged 18-25 years, with a population of 247,759 and a sample size of 270. The correlational method used to test the hypothesis in this study employs non-parametric analysis techniques. The research data will be analyzed using the JASP for Windows software. The analysis results from the Spearman Rho correlation coefficient show that the relationship between self-disclosure and social anxiety has a correlation coefficient of 0.033 and a P-Value of 0.590, indicating no significant relationship between self-disclosure and social anxiety. In contrast, the correlation coefficient between social comparison and social anxiety is 0.515, with a P-Value of 0.001, indicating a significant relationship between social comparison and social anxiety. This study contributes specifically to understanding the mechanisms of self-disclosure and social comparison underlying the emergence of social anxiety due to social media use, significantly advancing the field. The implications of this study include enhancing knowledge about self-disclosure and social comparison mechanisms that underlie increased social anxiety caused by social media use.